Inhibition Mechanism of Apigenin-8-C-glucoside on Starch Digestive Enzymes - CAO Shuyun, ZHENG Yuxue, CHAI Ziqi, YE Xingqian, TIAN Jinhu (Shipin Kexue, 2023)
The regulatory effect and mechanism of apigenin-8-C-glucoside on α-amylase and α-glucosidase activity were systematically investigated using enzyme activity kinetics, fluorescence spectroscopy, circular dichroism (CD) spectroscopy and molecular docking. Results indicated that apigenin-8-C-glucoside showed a good inhibitory effect on α-glucosidase in a non-competitive manner with a half-maximal inhibitory concentration (IC50) of 293.5 mg/L. However, no significant inhibitory effect on α-amylase was observed. Fluorescence spectroscopy showed that apigenin-8-C-glucoside could act as a quencher molecule to bind to α-glucosidase and quench its fluorescence statically, thereby changing the hydrophobic environment of the enzyme. The CD spectrum showed that the interaction between apigenin-8-C-glucoside and α-glucosidase loosened the secondary structure of this enzyme and decreased the contents of α-helix and β-turn. The results from molecular docking corroborated that the main interaction force between apigenin-8-C-glucoside and α-glucosidase was hydrogen bonding with a minimum binding energy of −7.2 kcal/mol. The present study provides a theoretical basis for the future development of apigenin-8-C-glucoside as an ingredient of health foods or drugs.